Impact of Lactoferrin Supplementation on Respiratory Tract Infections in Older Nursing Home Residents: A Protocol for a Randomized Control Trial. (7th June 2021) - Burton, Carl; Sigh, Vivek; Shahzad, Rabie; Lan, Esther; Brink, Lauren; Fawkes, Neil; Harris, Cheryl; Wu, Steven; Kirchoff, Ashlee; Ghadishah, Elham; Nemanim, Tatiana; Pham, Mai; et al.
Abstract: Objectives: To evaluate the impact of a dietary supplement within an elderly population who reside in a Community Living Center (CLC; VA Nursing Home), on the number of respiratory tract infections (RTIs) during a 90-day study period. Methods: This is a randomized, double-blind, placebo-controlled study to evaluate the impact of bovine Lactoferrin (bLf) on RTIs in an elderly nursing home population in the US. Subjects will be residents of the CLC and screened within 21 days prior to starting study supplementation. Eligible participants were at least 55 years of age, able to eat and drink and expected to reside at the CLC for the duration of the study. Consent was obtained from the study participant or their legally recognized representative decision maker. Participants will be excluded if: receiving tube feeds or specialized diets for eating disorders; immunocompromised; have a life expectancy of less than six months; or allergic to study products. Results: Subjects will be randomized in a ratio of 1:1 to either investigational (600 mg of bLf) or (placebo arms. All participants will take study supplement by mouth daily for 90 days. Subjects will be assessed daily for RTI symptoms. Blood and saliva will be collected at 45 and 90 days. Ad hoc assessments and a nasal sample will take place if a subject develops a protocol-defined RTI. Conclusions: The primary outcome will be number of RTIs over the 90-day study period. Secondary outcomes include severity and duration of RTI symptoms, symptoms associated with RTIs, number of RTI complications, and nasopharyngeal swab at onset of RTI, Other secondary outcomes include the following, all measured at baseline, day 45 and day 90: quality of life by questionnaire, weight, saliva markers, laboratory testing and immunological markers. An exploratory endpoint is vaccine specific inflammatory panel (influenza and Sars-Cov2) measured upon vaccination during supplement period. RTI number, severity, duration and complications and medically confirmed adverse events will be compared between the placebo and investigational groups. Funding Sources: RB/Mead Johnson & Company.